2002
DOI: 10.1017/s0014479702000248
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Performance of Animal-Drawn Implements for Minimum Tillage: Experience on Vertisols in Ethiopia

Abstract: Land degradation is one of the major problems related to low productivity in Ethiopia. Vertisols are potential agricultural lands but are underutilized due to waterlogging during the rainy season and are prone to soil erosion due to the traditional practices of planting crops at the end of the rainy season exposing bare land to heavy rains. An animal-drawn implement, the broadbed maker (BBM), was tested to facilitate drainage of the Vertisols. Improved drainage enables earlier planting of crops to use the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Mineral fertilising should not be the overall option, given scarce capital resources. Due to decreased landholdings, a shift in the soil tillage system to gardening and minimum tillage (on self-mulching Vertisols) may be suggested (Astatke et al 2002;Araya et al 2012), as well as an extension of the cropping period on Vertisols (Tedla et al 1999). Asnakew et al (1994) obtained good maize yields with rock fragment mulching and no-tillage.…”
Section: Agricultural Intensification and Land Rehabilitationmentioning
confidence: 99%
“…Mineral fertilising should not be the overall option, given scarce capital resources. Due to decreased landholdings, a shift in the soil tillage system to gardening and minimum tillage (on self-mulching Vertisols) may be suggested (Astatke et al 2002;Araya et al 2012), as well as an extension of the cropping period on Vertisols (Tedla et al 1999). Asnakew et al (1994) obtained good maize yields with rock fragment mulching and no-tillage.…”
Section: Agricultural Intensification and Land Rehabilitationmentioning
confidence: 99%
“…Eventually nine farmers participated in the on-farm trial during the 1999 cropping season, six of them from the original 12 and an additional three who did not participate in the earlier on-station demonstrations. The on-farm procedures following the 1999 cropping season have been reported by Astatke et al (2002a).…”
Section: Selection Of Farmersmentioning
confidence: 99%
“…Broadbed and furrow (BBF) technology, as it is known, was tested on-farm and later disseminated to farmers by the Ministry of Agriculture and several NGOs (Astatke et al, 2002a). At present, if farmers apply the BBF system on the same plot of land during consecutive seasons, the beds are destroyed by conventional tillage and reconstructed on an annual basis.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, Akbar et al (2007) reported about 36% water saving for broad-beds and about 10% for narrow-beds compared to flat sowing, and 6% increased grain yield of wheat and 33% of maize. In both cases, the furrows act as pathways for drainage during excessive rains and conserve rainwater in dry spells (Astatke et al, 2002). However, the use of direct dry seeding on flat and raised beds while resulting in considerable water savings generally had negative impacts on rice yield (Choudhury et al, 2007;Humphreys et al, 2010).…”
Section: In-situ Water Harvestingmentioning
confidence: 99%